Statistical modeling to unravel multiple predictors of the choice of chemotherapy for non-small cell lung cancer - Zhang, Zhongheng (Journal of Thoracic Disease, 2016)
Non-small cell lung cancer (NSCLC) is one of the leading causes of death worldwide (1). In north America, it is estimated that the standardized incidence rate (SIR) and the standardized mortality rate (SMR) of lung cancer equal to 23.1 and 19.7 (in 100,000 people), respectively (2).